Concurrent decisions on design concept and material selection using analytical hierarchy process at the conceptual design stage. - Salit, Mohd Sapuan; Ismail, Napsiah; Hambali, Ariff; Samsudin, Abdul Rahim; Yusoff, Nukman (2011)
There is an increased study for considering the precise decisions on the design concept (DC) and material concurrently at the early stage of development of product. Inappropriate decisions on DC and material always lead to huge cost involvement and ultimately drive toward premature component or product failure. To overcome this problem, concurrent engineering (CE) is an approach which allows designers to consider early decision making (EDM) need to be implemented. To illustrate the use of CE principle at the early stage of design process, a concept selection framework called concurrent DC selection and materials selection (CDCSMS) was proposed. In order to demonstrate the proposed CDCSMS framework, eight DC s and six different types of composite materials of automotive bumper beam have been considered. Both of these decisions were then verified by performing various scenarios of sensitivity analysis by using analytical hierarchy process through utilizing Expert Choice software.